Managing community engagement initiatives in health and social care: lessons learned from Italy and the United Kingdom. Issue 1 (4th January 2023) - Longo, Francesco; Barsanti, Sara; Bonciani, Manila; Bunea, Anita; Zazzera, Angelica
Abstract : Background: Determining the different features and potential impacts of community initiatives aimed at health-related outcomes poses challenges for both researchers and policy makers. Purpose: This article explores the nature of heterogeneous "community engagement initiatives" (CEIs) considering both their social and organizational features in order to understand the managerial and policy implications to maximize their potential local health and social care-related impacts. Methodology: A threefold qualitative analysis was conducted: (a) Three frameworks were developed to classify and analyze different CEIs features, building upon the current literature debate; (b) primary data were collected from Italian CEIs; and (c) a comparative cross-case analysis of a total of 79 CEIs in Italy and the United Kingdom was implemented. Findings: The results show two types of strategic policy and management implications: (a) CEI portfolios are very broad and differentiated; (b) different social networks have diversified social constructs, internal cultures, and organizational features; and (c) there is a consequent need to contextualize relational and steering approaches in order to maximize their potential community added value. Conclusion: CEIs are fundamental pillars of contemporary welfare systems because of both the changing demography and epidemiology and the disruptive impact of platform economy models. This challenging scenario and the related CEIs involve a complex social mechanism, which requires a new awareness and strengthened competences for public administrations' steering. Practice Implications: It is crucial for policy makers and managers to become familiar with all the different CEIs available in order to choose which solution to implement, depending on their potential impacts related to local public health and social care priorities. They also need to select the related effective steering logic.